Economic evaluations of maternal health interventions: a scoping review [version 2; peer review: 2 approved] - Sher Ting Chim; Steve McDonald; Rana Islamiah Zahroh; Katherine E. Eddy; Alexander Eggleston; Joshua P. Vogel; Doris Chou; Olufemi T. Oladapo; Caroline S. E. Homer; Nick Scott; Elizabeth Sebastian; Chloe Bykersma (F1000Research)
Background Evidence on the affordability and cost-effectiveness of interventions is critical to decision-making for clinical practice guidelines and development of national health policies. This study aimed to develop a repository of primary economic evaluations to support global maternal health guideline development and provide insights into the body of research conducted in this field. Methods A scoping review was conducted to identify and map available economic evaluations of maternal health interventions. We searched six databases (NHS Economic Evaluation Database, EconLit, PubMed, Embase, CINAHL and PsycInfo) on 20 November 2020 with no date, setting or language restrictions. Two authors assessed eligibility and extracted data independently. Included studies were categorised by subpopulation of women, level of care, intervention type, mechanism, and period, economic evaluation type and perspective, and whether the intervention is currently recommended by the World Health Organization. Frequency analysis was used to determine prevalence of parameters. Results In total 923 studies conducted in 72 countries were included. Most studies were conducted in high-income country settings (71.8%). Over half pertained to a general population of pregnant women, with the remainder focused on specific subgroups, such as women with preterm birth (6.2%) or those undergoing caesarean section (5.5%). The most common interventions of interest related to non-obstetric infections (23.9%), labour and childbirth care (17.0%), and obstetric complications (15.7%). Few studies addressed the major causes of maternal deaths globally. Over a third (36.5%) of studies were cost-utility analyses, 1.4% were cost-benefit analyses and the remainder were cost-effectiveness analyses. Conclusions This review provides a navigable, consolidated resource of economic evaluations in maternal health. We identified a clear evidence gap regarding economic evaluations of maternal health interventions in low- and middle-income countries. Future economic research should focus on interventions to address major drivers of maternal morbidity and mortality in these settings.